THE APPLICATION OF SAMR MODEL AND SELF-EFFICACY ON CRITICAL THINKING AND PROCEDURAL KNOWLEDGE - Alfiana, Herlia; Karyono, Hari; Gunawan, Wawan (LLT Journal: A Journal on Language and Language Teaching, 2022)
The use of e-learning presents new challenges for students in terms of improving their critical thinking skills and procedural knowledge in grammar learning. As a result, lecturers need a specific framework while creating an e-learning course. The application of SAMR model is a solution. One of the most dominant traits among students is and self-efficacy. The level of student self-efficacy was controlled in this study to measure the effect of using the SAMR model. This study uses a quasi-experimental design with a factorial design. This study involved 152 students in the experimental and control groups. The research analysis technique was tested using MANOVA. The results and conclusions show that: (1) the SAMR model has a significant effect on students' critical thinking skills and procedural knowledge; (2) self-efficacy significantly affects students' critical thinking skills and procedural knowledge; and (3) a combination of learning models and self-efficacy has a significant effect on procedural knowledge, but does not significantly affect critical thinking skills. This study contributes and improves the quality of e-learning implementation techniques, particularly in the area of English learning.